La gestación subrogada: una vulneración de los derechos humanos y libertades fundamentales de la mujer en Colombia (2020)
Surrogacy is a practice by means of which a woman carries a baby for another person or partner so that the latter can be a mother and/or biological father. Surrogacy is an increasingly common practice in Colombia. Therefore, the main objective of this research is to analyze this practice in the Colombian State. In the present work, the socio-legal paradigm, the hermeneutical method, and a section of analytical research were used. From the analysis it is verified, firstly, that in Colombia three bills have been promulgated to regulate the practice of surrogacy, but none had the necessary support; secondly, that there is a landmark judgment of the Constitutional Court on the practice of surrogacy, establishing the requirements in which such practice could occur; thirdly, that according to the Political Constitution of Colombia, surrogacy implies the violation of certain fundamental rights and that, according to civil law, it does not comply with what is stipulated in relation to contracts; fourthly, that surrogacy implies the violation of human rights. It is concluded that the State of Colombia should prohibit the practice of surrogacy since it involves the violation of fundamental and human rights enshrined in international conventions, as well as established in the Constitution.